Information, communication and computing technology : second International Conference, ICICCT 2017, New Delhi, India, May 13, 2017, Revised selected papers /: second International Conference, ICICCT 2017, New Delhi, India, May 13, 2017, Revised selected papers. (2017) - Unknown
No abstract available